KEDUDUKAN DAN FUNGSI TENTARA NASIONAL INDONESIA (TNI) DALAM SISTEM KETATANEGARAAN REPUBLIK INDONESIA - , Priyo Hadisusilo, SH, Sardjuki, SH., MH. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of this study is to investigate and assess the position of the Indonesian National Army (TNI) in the constitutional system of the Republic of Indonesia, the TNI functions only as a means of national defense in the constitutional system of the Republic of Indonesia, and the constraints faced by the Indonesian military (TNI) in implementing the military function in the constitutional system of the Republic of Indonesia. This type of research is normative and empirical legal research with normative research model, the research with the object of study of the position and function of the Indonesian National Army (TNI) in the constitutional system of the Republic of Indonesia. Data has been collected from the research, both literature research and field research, will be legally qualitative analysis, which is a method of data analysis by classifying and selecting the data obtained from the study according to the quality and truth, then connected with legislation and theories derived from the study of literature, in order to obtain answers to the problems in this study The results of this study are: (1) a new paradigm military position in the constitutional system of the Republic of Indonesia realized through Law No. 34 of 2004 on the Indonesian National Armed Forces passed the House of Representatives (30 September 2004) has been doing construction re-formulation of military duty.